Analysis of Formal Errors in Visum et Repertum and Their Legal Consequences on the Evidential Value in Criminal Cases of Assault (Study of Decision No. 309/Pid.B/2024/PN. BJM) - Najwa Maulida Sabrina; Hery Firmansyah (Jurnal Daulat Hukum, 2025)
The criminal act of assault is a prevalent offense in society and is regulated under Articles 351 to 354 of the Criminal Code (KUHP). In the evidentiary process of assault cases, the Visum et Repertum (VER) serves a critical role as both documentary evidence and expert testimony, as specified in Articles 133 and 184 of the Indonesian Criminal Procedure Code (KUHAP). However, the admissibility of VER requires compliance with both formal and substantive standards in accordance with medical and legal norms. This study examines formal defects in VER and their legal implications for evidentiary value, using Case Decision No. 309/Pid.B/2024/PN BJM as a case study. The findings reveal that the VER was issued based on a Visum Request Letter (SPV) signed by an unauthorized investigator, and its contents failed to meet the requirements of the Indonesian Medical Competency Standards (SKDI). Despite these deficiencies, the court relied on the VER as the basis for conviction, even though the case lacked two valid pieces of evidence and no witness directly observed the alleged crime. This research concludes that formal defects in VER can undermine the principles of legality and legal certainty, and may violate the defendant's fundamental rights.